Long-term, low emission and climate resilient development pathways - Chesterman, Sabrina; Chevallier, Romy; Neely, Constance (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Climate change presents one of the biggest threats to sustainable development worldwide. Its widespread unprecedented impacts disproportionately burden the poorest and most vulnerable majority – a significant number of whom live in Africa. The most prominent global policy response to climate change is currently covered by the United Nations Framework Convention on Climate Change (UNFCCC). There is clear evidence that Africa is constrained by its limited capacity to effectively participate in the international climate change policy discourse to foster climate actions at regional and national levels. Climate change diplomacy and negotiations are often technical and complex. It is difficult for new negotiators to fully grasp the nuances of the proceedings even over a period of many years. The African Group of Negotiators Expert Support (AGNES) has designed this training Program on climate governance, diplomacy and negotiations leadership with a view to address this important continental challenge. This is a call for applications to eligible applicants.